Impacts of direction and morphological locus of control on learnability of sibilant harmony - Elliot Stork; Jenna Conklin; Ruken Bastimar; Xueqi He (Laboratory Phonology)
A notable cross-linguistic gap exists in the typology of consonant harmony: Stem-controlled and suffix-controlled systems are known, but prefix-controlled consonant harmony remains unattested. To explore this gap, an artificial grammar learning (AGL) study was conducted, in which participants were passively trained and then tested on one of four possible sibilant harmony patterns, differing by direction and morphological locus of control. The effect of target-trigger distance was also tested by varying the stem length from one to four syllables. Statistical analysis found significant main effects of Direction and Target-Trigger Distance, with the progressive group outperforming the regressive one and shorter target-trigger distances yielding better performance than longer ones. Affix-controlled groups also learned the pattern more slowly than stem-controlled groups, although overall performance did not differ between affix-controlled and stem-controlled groups. Overall, the results indicate that the typological lack of prefix-controlled consonant harmony is not due to a lack of learnability, as there was no statistically significant difference in ultimate achievement between the four groups.